Intermarriage and the economic success of immigrants - Olga Nottmeyer (IZA World of Labor, 2015)
Marriages between immigrants and natives (intermarriages) are often associated with economic success and interpreted as an indicator of social integration. Intermarried immigrant men are on average better educated and work in better paid jobs than nonintermarried immigrant men. In this context, native spouses could deliver valuable insights into the host country and provide business contacts. However, intermarriage may not be the driving factor of economic success but instead be its byproduct, as better education and personal characteristics could be both economically beneficial and increase the likelihood of meeting natives. Intermarriage might also be more “suspense-packed” (positively and negatively) and can thus be associated with an increase in severe stress and a higher risk of divorce.
Keywords: J12; 330; integration; education; immigration; marriage